2017
DOI: 10.21037/cdt.2017.03.21
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 versus type 1 myocardial infarction: a comparison of clinical characteristics and outcomes with a meta-analysis of observational studies

Abstract: Background: Type 2 myocardial infarction (MI) is an imbalance between myocardial oxygen demand and supply, leading to myocardial ischemia. It is not due to plaque rupture, and is usually caused by a condition other than coronary artery disease (CAD). However, limited data are available comparing the prevalence of traditional coronary risk factors and mortality between type 1 and type 2 MI. We hypothesize that type 2 MI carries a higher mortality than type 1. Methods:We searched the databases of PubMed, EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
3
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 38 publications
4
71
3
4
Order By: Relevance
“…In the TRACER trial, the most frequent potential provoking factor for T2MI was tachyarrhythmia (38.2%), which is consistent with our findings . A meta‐analysis also demonstrated that the most common associated arrhythmia was tachyarrhythmia, especially atrial fibrillation, in patients with T2MI . Most patients with T2MI died from noncardiovascular causes during long‐term follow‐up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the TRACER trial, the most frequent potential provoking factor for T2MI was tachyarrhythmia (38.2%), which is consistent with our findings . A meta‐analysis also demonstrated that the most common associated arrhythmia was tachyarrhythmia, especially atrial fibrillation, in patients with T2MI . Most patients with T2MI died from noncardiovascular causes during long‐term follow‐up.…”
Section: Discussionsupporting
confidence: 89%
“…In this review, most selected studies revealed that the number of men with T2MI was higher than that of women, while a reduced number of studies found the opposite . For example, Gupta et al described T2MI was more common in females compared with T1MI . Among the clinical characteristics of T2MI, we concluded that cardiovascular risk factors or comorbidities might be the most important causes of T2MI and affect the prognosis in these patients.…”
Section: Discussionmentioning
confidence: 73%
“…Both type 1 and type 2 MI can present as NSTEMI or STEMI, although NSTEMI is more common for both types . Most NSTEMI pathophysiologically are consistent with type 1 MI, but the relative proportions of type 1 NSTEMI and type 2 NSTEMI vary between clinical settings …”
Section: Discussionmentioning
confidence: 99%
“…NSTEMI is more common than STEMI, although the proportion of patients with STEMI is higher for type 1 MI than type 2 . A meta‐analysis of observational studies comparing type 1 and type 2 MI showed that 70.0% of the 2683 patients with type 2 MI were diagnosed with NSTEMI compared with 44.1% of 23 189 patients with type 1 MI . A prospective study of consecutive patients meeting the definition of MI found that 96.7% of the 144 patients with type 2 MI had NSTEMI, compared with 67.3% of the 397 patients with type 1 MI .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation